Observation of saturation transfer characteristics in solution processed vertical organic field-effect transistors (VOFETs) with high leakage current - Mohd Sarjidan, Mohd Arif; Shuhaimi, Ahmad; Abd Majid, Wan Haliza (Elsevier, 2018)
Unlike ordinary organic field-effect transistors (OFETs), saturation current is hardly to be found in vertical OFETs (VOFETs). Moreover, the fabrication process of patterned sourced for VOFETs is quite complex. In this current work, a simple solution processed VOFET with directly deposited intermediate silver source electrode has been demonstrated. The VOFET exhibits a high leakage current that induces an inversion polarity of its transistor behavior. Interestingly, a well-defined saturation current was observed in the linear scale of transfer characteristic. The VOFET operated with high-current density >280 mA/cm2 at Vd = 5 V. Overview potential of the fabricated device in display application is also presented. This preliminary work does open-up a new direction in VOFET fabrication and their application.